Foreign equity flows and stock market liquidity in Kenya - Rogers Ondiba Ochenge; Rose W. Ngugi; Peter Muriu (Cogent Economics & Finance, 2020)
In this paper, we explore the dynamic relationship between aggregate foreign equity inflows and aggregate liquidity of the Kenyan stock market using transactional foreign trading data and several liquidity measures. We employ vector autoregression with monthly gross foreign inflows, local stock market liquidity and returns over the period 2011-2018. We discover a one-way causality link from inflows to liquidity and that foreign investors promote rather than impede local liquidity. Our analysis therefore renders support to the recent policy by Capital Market Authority of Kenya that now allows foreign investors to acquire up to 100% of any stock listed at the Kenyan stock exchange market.
Keywords: G12; G180; 330; Foreign equity inflows; stock market liquidity; vector autoregression